Study of Length-Weight Relationship and Condition Factor of Sandfish Sea Cucumber (Holothuria scabra) - Andy Rasyadi; Etty Riani; Sigid Hariyadi; Neri Kautsari (Jurnal Penelitian Pendidikan IPA, 2023)
The overfishing of the sandfish Holothuria scabra is increasing due to its various benefits, thus reducing its population in nature. This study aimed to examine sandfish's length-weight relationship and condition factors on the North Coast of Sumbawa Island, with sampling locations at two stations, Ai Limung (Pungkit Village), and Labu Prajak (Batu Bangka Village). The study was conducted in September-October 2022. A total of 142 specimens were obtained from both stations, 122 samples at Ai Limung station (mean length 9.22±2.12 cm; weight 43.34±25.07 grams). Then 20 samples at the Labu Prajak station (mean length 13.69±3.74 cm; weight 88.70±60.06 grams). Growth patterns of each research station are negative allometric, indicating the body length of the sandfish grows faster than its weight. Condition factor at Ai Limung station Kn=1.03±0.26, Wr=1.03±0.26, K=5.33±1.76, and at the Labu Prajak station Kn=1.05±0.28, Wr=104.88±27.83, K=3.27±1.14. The results showed significant differences in length, weight, and fulton condition factor. The mean body length and weight of sandfish at both stations are smaller than previous study, indicating the earlier sign of overfishing. Meanwhile, the fulton condition factor at Ai Limung station showed a higher value, which indicated the location was better, with abundant food sources and fewer predators